Perancangan Garden Walk Shopping Mall Dengan Pendekatan Arsitektur Biophilic Di Bogor, Jawa Barat - Indira Yulianti; Putri Suryandari; Anggraeni Dyah Sulistiowati (FAKULTAS TEKNIK UNIVERSITAS BUDI LUHUR, 2022)
Garden Walk Shopping Mall Design With a Biophilic Architectural Concept is a building whose main function is as a means of entertainment and recreation to facilitate modern shopping activities. A shopping mall is a space that can be used as a shopping and recreation center consisting of several shopping complexes in which buying and selling activities occur as well as the exchange of goods and services as well as a gathering place. By applying Biophilic principles such as Nature in space and Natural analogues so that this Shopping mall building can maintain the psychological and psychological health of its visitors. such as the shape of the avoid leaf plant, through this form a biophilic pattern will be achieved. This underlies the reason for applying the concept of biophilic architecture which has a positive relationship with nature. Located in the city of Bogor which is famous for its tourism potential and natural beauty, it is expected to be a means to meet the needs of modern shopping, entertainment and recreation that is capable of being a means to respond to a positive relationship with nature through modern shopping facilities by applying biophilic principles so as to respond positively to nature. good relationship between humans and nature. Keywords: Garden Walk Shopping Mall, Shopping Mall, Biophilic Architecture, Bogor